Studi Sintesis Analog Piokelin III: Sintesis Asam 3-Asetil-2-(2-(2-Hidroksifenil)- 4,5-Dihidrotiazol-4-Il)Tiazolidine-4-Karboksilat - Zamri, Adel (Jurnal Natur Indonesia, 2007)
The total syntheses of 3-acetyl-2-(2-(2-hydroxyphenyl)-4,5-dihydrothiazole-4-yl) thiazolidine-4-carboxylic acid, a new pyochelin analog is described. The molecule intermediate 4’-(2-hydroxy-phenyl)-2,3,4,5,2’,5,-hexahydro- [2,2’]bithiazolil-4-carboxylic acid was obtained in 4 steps reaction from 2-hydroxybenzonitrile in good yields. The Nacetylation of molecule intermediate was carried out by acetic anhydride to produce pyochelin analog in moderate yields.